Online self-management for gay men living with HIV: A Pilot Study - Millard, T.; McDonald, K.; Girdler, Sonya; Slavin, S.; Elliot, J. (2015)
Background: The aim of this pilot study was to assess the feasibility, acceptability and effectiveness of Positive Outlook, an online self-management program for gay men living with HIV in Australia. Methods: Two pilot studies were conducted, a small feasibility study (Pilot 1) followed by a pilot randomised controlled study (Pilot 2). Pilot 1 employed a pre and post-test design and included 10 men. Within- and between-group differences were evaluated in Pilot 2, which involved 37 participants randomly assigned to receive the Positive Outlook Program or usual care. We report on feasibility, acceptability and a range of preliminary efficacy outcomes, including health education impact, HIV-related quality of life and HIV-related self-efficacy. Results: The program was well accepted by participants with some decline in engagement with the discussion boards witnessed over the duration of the program. Overall, intervention group participants demonstrated improvements in the majority of efficacy outcome measures, including HIV-related quality of life, self-efficacy, self-management skills, social support and adjustment to HIV. Conclusion: These pilot studies demonstrated that an online program to facilitate self-management among gay men living with HIV is both feasible and well accepted by participants who persisted with the program per protocol. Preliminary data suggest that the Positive Outlook program has the potential to enhance participants’ quality of life, self-efficacy and health related outcomes, and demonstrates the need for further study with a larger sample.